Topographic and morphometric characterization of the humerii nutrient foramina and their implications for fracture repair and healing - Pedzisai Mazengenya; Palesa Mokoena; Brendon Kurt Billings; Arthur Tsalani Manjatika (Scientific Reports)
Abstract Fractures of the humerus are common on the midshaft of the bone, often causing injury to the nutrient artery. Successful fracture repair and healing requires preservation of the blood supply to the long bones which is conveyed through the nutrient foramina (NF). The topography of long bone NF varies in different populations. These variations can affect the preservation of blood supply to long bones during fracture repair management. The current study aimed to determine the topography and morphometry of the NF of the humerus in different populations of South Africa including the South African Africans (SAA), South Africans of European descent (SAED), and South Africans of mixed ancestry (SAMA). The study examined 596 dry humerii from the three South African populations, sourced from Raymond A. Dart Collection of Modern Human Skeletons. The parameters examined included the presence, number, location, position, size and direction of the NF, and foramina index (FI). The NF were present in 97.1% of the humerii. Majority of bones (76.8%) evinced a single NF with a diameter equal to or larger than 1.27 mm. The number of NF varied across the different population groups (p = 0.000), with SAA having more humerii presenting with a single NF and SAED having more humerii with two NF. The position of NF varied within and across populations (p = 0.002). Males in SAED had a higher mean FI on both the right (p = 0.030) (effect size = 0.258) and left (p = 0.022) (effect size = 0.421) sides than females. SAED had a lower mean FI than SAMA (p = 0.002) (effect size = 0.384). The location of NF varied across different populations (p = 0.000), with SAA having more NF located on the anteromedial surface and medial border, and SAED having more NF located on the lateral border (p = 0.000). NF were directed towards the distal ends of the shafts in 99.8% of bones and towards the proximal end in 0.2% of bones. The topography and morphometry of the nutrient foramina of the humerus are variable in the South African populations. Knowledge of the NF variations may aid in the management of humerus fractures.